Analysis of Agro-Service Provision and Resource Utilization Efficiency in Cotton-Textile Clusters - Turdibayevna, Kudratova Iroda (American Journal of Biodiversity, 2025)
This article examines the current state of agro-service provision and resource utilization efficiency within cotton-textile clusters in Uzbekistan. These clusters integrate agricultural production and textile manufacturing into a unified value chain, aiming to increase productivity, reduce costs, and improve competitiveness. Based on empirical data from Fergana, Andijan, and Kashkadarya regions, the study identifies key disparities in the quality and availability of agro-services such as mechanization, irrigation, and input supply. The research also highlights significant inefficiencies in land, water, and labor utilization, especially in clusters lacking modern technologies. Comparative analysis between technologically advanced and traditional clusters demonstrates that digitalization, centralized service coordination, and smart technologies significantly enhance performance. The study applies both quantitative and qualitative methods, including statistical analysis, field surveys, and expert interviews. The findings emphasize the need for improved agro-service governance, investment in agri-tech infrastructure, and stronger stakeholder coordination to unlock the full potential of cotton-textile clusters. Ultimately, enhanced agro-service delivery and efficient resource use are critical to achieving sustainable growth, higher yields, and increased export potential in Uzbekistan’s agricultural-industrial complex.